2011
DOI: 10.1007/s00520-011-1226-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings of palonosetron in cancer patients

Abstract: In this study, we revealed that palonosetron did not cause any severe rhythmic disorders or symptomatic ECG changes. We concluded that it could be safe to administer palonosetron antiemetically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
(35 reference statements)
2
33
0
Order By: Relevance
“…13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy. The primary objective of this study was to demonstrate in paediatric patients the non-inferiority of palonosetron, versus ondansetron, during the acute phase of the first on-study chemotherapy cycle.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy. The primary objective of this study was to demonstrate in paediatric patients the non-inferiority of palonosetron, versus ondansetron, during the acute phase of the first on-study chemotherapy cycle.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to laboratory values, vital signs, and ECG findings, there were no pronounced differences between palonosetron and older 5-HT 3 RAs. The studies analyzed here did not thoroughly evaluate QTc measures; however, recent studies in patients with cancer 17,18 and a thorough QTc study in healthy subjects that used a positive control (ie, moxifloxacin) 16 demonstrated no significant QTc changes associated with palonosetron. This is in contrast to evidence of significant dose-related QTc prolongation with ondansetron, which led to the removal of the 32-mg single dose from its label, 30 and an increased risk of cardiac arrhythmias with IV dolasetron, which is no longer recommended.…”
Section: Discussionmentioning
confidence: 99%
“…As the first combination antiemetic developed, it targets two critical molecular pathways (substance P/NK 1 RA; serotonin/5-HT 3 RA) associated with CINVand offers guidelineconsistent prophylaxis with a single dose (and DEX). Palonosetron was selected for the combination over older generation 5-HT 3 RAs due to its distinctive pharmacological properties [20,21], safe cardiac profile [22][23][24][25], and proven clinical efficacy [26][27][28][29]. In mechanistic studies, netupitant and palonosetron have exhibited synergistic effects when inhibiting the substance P response [30].…”
Section: Evaluation Of Nepa In Patients Receiving Carboplatinmentioning
confidence: 99%